Identification of a novel hydrolase encoded by hy-1 from Bacillus amyloliquefaciens for bioremediation of carbendazim contaminated soil and food - Li, Ying; Chi, Miaomiao; Ge, Xizhen (International Journal of Agricultural and Biological Engineering, 2019)
Carbendazim (MBC) is an effective antifungal and antibacterial pesticide in agricultural applications. However, the MBC-contaminated soil and food are difficult to be restored. In this work, a novel MBC-hydrolase HY-1 encoded by gene hy-1 from an isolated MBC-degrading bacteria Bacillus amyloliquefaciens has been screened and identified. The 858 bp hydrolase gene was expressed in E. coli BL21 and the 32 kDa hydrolase HY-1 was purified. The purified HY-1 was able to catalyze MBC into 2-aminobenzimidazole (2-AB) without the need for any cofactors. Then bioremediation experiment was conducted and both the strain Car4 and cell crude extract of E. coli (pET-hy1) accelerated MBC degradation in soil. Moreover, purified HY-1 was available in removing MBC residue on the surface of cucumber. This work explored the possibility of microbial and enzymatic bioremediation on MBC-contaminated soil and food, provide a new way for bioremediation of pesticide contaminations.Keywords: carbendazim, bioremediation, antifungal and antibacterial pesticide, hydrolase, soil, food, pesticide contaminationDOI: 10.25165/j.ijabe.20191202.4190Citation: Y Li, M M Chi, X Z Ge. Identification of a novel hydrolase encoded by hy-1 from Bacillus amyloliquefaciens for bioremediation of carbendazim contaminated soil and food. Int J Agric & Biol Eng, 2019; 12(2): 218–224.